Cell Cycle Aberration in Ameloblastoma: as Evidenced by an Immunohistochemical Expression of P53 and Survivin (Global Journal of Medical Research, 2014)
Evasion from apoptosis by aberrations of apoptotic regulatory factors has been found to cause accumulation of neoplastic cells in various tumours. Survivin, an inhibitor of apoptosis protein localizes to the nucleus as well as in the cytoplasm depending on its function such as cell division and inhibiting apoptosis. The regulation of Survivin seems to be linked to p53, a tumour suppressor gene. Though there are studies showing the role of p53 and Survivin in oral carcinogenesis, but the field of odontogenic tumours yet needs to be explored. The aim of this study was to correlate the expression of p53 and Survivin in normal tissues (tooth germ) and Ameloblastoma as well as to assess differential localization of Survivin. Qualitative and quantitative assess-ment of immunexpression of p53 and Survivin (nuclear and cytoplasmic) was evaluated in a total of 35 cases which included 10 tooth germs and 25 Ameloblastoma. The expression levels of p53 and nuclear Survivin were significantly higher in Ameloblastoma quantitatively but there was no significant correlation between p53 and cytoplasmic expression of Survivin.
Keywords: apoptosis; survivin; p53; ameloblastoma; immunohistochemical expression; tumorigenesis; aberrations; tumour suppressor gene; inhibitor of apoptosis pr